Mediating the effect of cognitive flexibility in the relationship between psychological well-being and self-confidence: A study on Turkish university students - Malkoç, Asude; Kesen Mutlu, Aynur (Sciedu Press, 2019)
This study examined the role of self-confidence and cognitive flexibility in psychological well-being. The study looked into whether cognitive flexibility mediates the relationship between self-confidence and psychological well-being. The study involved the participation of 284 university students (192 female and 92 male) enrolled in the Faculty of Education at a private university in Istanbul, Turkey. Data was collected via the Self-Confidence Scale, Flourishing Scale and Cognitive Flexibility Scale. The results of our multiple regression analysis revealed that self-confidence and cognitive flexibility statistically predict psychological well-being. Self-confidence and cognitive flexibility were found to explain 38% of the variance in psychological well-being. Furthermore, cognitive flexibility served as a mediator in the relationship between self-confidence and psychological well-being.
Keywords: Self-Confidence; Psychological Well-Being; Cognitive Flexibility; University Students